Beta-Sitosterol Facilitates GLUT4 Vesicle Fusion on the Plasma Membrane via the Activation of Rab/IRAP/Munc 18 Signaling Pathways in Diabetic Gastrocnemius Muscle of Adult Male Rats - JinJin Pei; Monisha Prasad; Ghada Mohamed Helal; Mohamed El-Sherbiny; Dalia Mahmoud Abdelmonem Elsherbini; Ponnulakshmi Rajagopal; Chella Perumal Palanisamy; Vishnu Priya Veeraraghavan; Selvaraj Jayaraman; Krishna Mohan Surapaneni (Bioinorganic Chemistry and Applications)
Nutritional overload in the form of high-fat and nonglycolysis sugar intake contributes towards the accelerated creation of reactive oxygen species (ROS), hyperglycemia, and dyslipidemia. Glucose absorption and its subsequent oxidation processes in fat and muscle tissues alter as a consequence of these modifications. Insulin resistance (IR) caused glucose transporter 4 (GLUT4) translocation to encounter a challenge that manifested itself as changes in glycolytic pathways and insulin signaling. We previously found that beta (β)-sitosterol reduces IR in fat tissue via IRS-1/PI3K/Akt facilitated signaling due to its hypolipidemic and hypoglycemic activity. The intention of this research was to see whether the phytosterol β-sitosterol can aid in the translocation of GLUT4 in rats fed on high-fat diet (HFD) and sucrose by promoting Rab/IRAP/Munc 18 signaling molecules. The rats were labeled into four groups, namely control rats, HFD and sucrose-induced diabetic control rats, HFD and sucrose-induced diabetic rats given oral dose of 20 mg/kg body wt./day of β-sitosterol treatment for 30 days, and HFD and sucrose-induced diabetic animals given oral administration of 50 mg/kg body wt./day metformin for 30 days. Diabetic rats administered with β-sitosterol and normalized the titers of blood glucose, serum insulin, serum testosterone, and the status of insulin tolerance and oral glucose tolerance. In comparison with the control group, β-sitosterol effectively regulated both glycolytic and gluconeogenesis enzymes. Furthermore, qRT-PCR analysis of the mRNA levels of key regulatory genes such as SNAP23, VAMP-2, syntaxin-4, IRAP, vimentin, and SPARC revealed that β-sitosterol significantly regulated the mRNA levels of the above genes in diabetic gastrocnemius muscle. Protein expression analysis of Rab10, IRAP, vimentin, and GLUT4 demonstrated that β-sitosterol had a positive effect on these proteins, resulting in effective GLUT4 translocation in skeletal muscle. According to the findings, β-sitosterol reduced HFD and sucrose-induced IR and augmented GLUT4 translocation in gastrocnemius muscle through insulin signaling modulation via Rab/IRAP/Munc 18 and glucose metabolic enzymes. The present work is the first of its kind to show that β-sitosterol facilitates GLUT4 vesicle fusion on the plasma membrane via Rab/IRAP/Munc 18 signaling molecules in gastrocnemius muscle.